P2Y12 inhibitor monotherapy or dual antiplatelet therapy after coronary revascularisation: individual patient level meta-analysis of randomised controlled trials. (16th June 2021) - Valgimigli, Marco; Gragnano, Felice; Branca, Mattia; Franzone, Anna; Baber, Usman; Jang, Yangsoo; Kimura, Takeshi; Hahn, Joo-Yong; Zhao, Qiang; Windecker, Stephan; Gibson, Charles M; Kim, Byeong-Keuk; et al.
Abstract: Objective: To assess the risks and benefits of P2Y12 inhibitor monotherapy compared with dual antiplatelet therapy (DAPT) and whether these associations are modified by patients' characteristics. Design: Individual patient level meta-analysis of randomised controlled trials. Data sources: Searches were conducted in Ovid Medline, Embase, and three websites (www.tctmd.com, www.escardio.org, www.acc.org/cardiosourceplus ) from inception to 16 July 2020. The primary authors provided individual participant data. Eligibility criteria: Randomised controlled trials comparing effects of oral P2Y12 monotherapy and DAPT on centrally adjudicated endpoints after coronary revascularisation in patients without an indication for oral anticoagulation. Main outcome measures: The primary outcome was a composite of all cause death, myocardial infarction, and stroke, tested for non-inferiority against a margin of 1.15 for the hazard ratio. The key safety endpoint was Bleeding Academic Research Consortium (BARC) type 3 or type 5 bleeding. Results: The meta-analysis included data from six trials, including 24 096 patients. The primary outcome occurred in 283 (2.95%) patients with P2Y12 inhibitor monotherapy and 315 (3.27%) with DAPT in the per protocol population (hazard ratio 0.93, 95% confidence interval 0.79 to 1.09; P=0.005 for non-inferiority; P=0.38 for superiority; τ 2 =0.00) and in 303 (2.94%) with P2Y12 inhibitor monotherapy and 338 (3.36%) with DAPT in the intention to treat population (0.90, 0.77 to 1.05; P=0.18 for superiority; τ 2 =0.00). The treatment effect was consistent across all subgroups, except for sex (P for interaction=0.02), suggesting that P2Y12 inhibitor monotherapy lowers the risk of the primary ischaemic endpoint in women (hazard ratio 0.64, 0.46 to 0.89) but not in men (1.00, 0.83 to 1.19). The risk of bleeding was lower with P2Y12 inhibitor monotherapy than with DAPT (97 (0.89%) v 197 (1.83%); hazard ratio 0.49, 0.39 to 0.63; P<0.001; τ 2 =0.03), which was consistent across subgroups, except for type of P2Y12 inhibitor (P for interaction=0.02), suggesting greater benefit when a newer P2Y12 inhibitor rather than clopidogrel was part of the DAPT regimen. Conclusions: P2Y12 inhibitor monotherapy was associated with a similar risk of death, myocardial infarction, or stroke, with evidence that this association may be modified by sex, and a lower bleeding risk compared with DAPT. Registration: PROSPERO CRD42020176853.